Pengaruh Kepemimpinan dan Lingkungan Kerja Terhadap Kinerja Karyawan PT. Hindoli Estate Pulai Berayun - Anggraini, Risna; Amidi; Agusria, Lesi (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2025)
This study aims to determine the Influence of Leadership and Work Environment on Employee Performance at PT. Hindoli Estate Pulai Berayun. This type of research is associative. The population in this study was 87 employees, with a sample of 47 employees. The data used in this study were primary and secondary data. The data collection method used a questionnaire. The analysis technique used was Multiple Linear Regression Analysis. The results of this study are: 1) There is a significant influence of leadership and work environment together on employee performance at PT. Hindoli Estate Pulai Berayun 2) There is a significant influence of leadership together on employee performance at PT. Hindoli Estate Pulai Berayun 3) There is a significant influence of work environment together on employee performance at PT. Hindoli Estate Pulai Berayun